Fatigue crack growth in natural rubber: The role of SIC investigated through post-mortem analysis of fatigue striations. (1st October 2018) - Ruellan, B.; Le Cam, J.-B.; Robin, E.; Jeanneau, I.; Canévet, F.; Mauvoisin, G.; Loison, D.
Highlights: Striations form on the failure surfaces of crystallizable rubbers. The link between SIC and striations is investigated. They do not appear at 90 °C and require therefore that the material is crystallizing. Striations are not the signature of SIC in the lifetime reinforcement. Abstract: Fatigue striations are investigated in order to provide additional information on the role of SIC in the fatigue crack growth resistance in natural rubber (NR). Uniaxial fatigue tests were carried out with Diabolo samples under a wide range of loading ratios and loading levels. Fracture surfaces were analyzed by using SEM. Two striation regimes were identified: small striation patches with different orientations (Regime 1) and zones with large and well formed striations, where wrenchings are no longer observed (Regime 2). As fatigue striations were observed for all the loading ratios applied, they are therefore not the signature of SIC in the lifetime reinforcement. Nevertheless, increasing the minimum value of the strain amplified the striation phenomenon and the occurrence of Regime 2. Results obtained have been qualitatively put into perspective with crack propagation curves provided in Lindley (1973). The analysis carried out unifies the results obtained in the literature for relaxing and fully relaxing loadings ( R ε ⩽ 0 ) in the sense that increasing the loading, i.e. the tearing energy, leads to an increase in the crack growth rate and to a striation typology evolution, especially the striation size. For non-relaxing loadings, our results suggest that the striation typology may be governed by the loading ratio rather than the crack growth rate. Finally, as striations did not appear when the tests were performed at temperature superior or equal to 90 ° C, the formation of striation requires therefore that the material is crystallizing.